Eksplorasi Niat Bepergian Wisatawan Muslim: Studi Kasus Masyarakat Muslim Kota Batam yang Akan Berkunjung ke Pulau Bali - Sihombing, Dame Afrina; Hariyanto, Oda Ignatius Besar; Kristina, Theresia Dwi (EKONOMI KEUANGAN DAN BISNIS, 2024)
Indonesia is a country that has a variety of tribes and cultures. One of the important industries for Indonesia's growth is the tourism sector, the tourism industry in question is hotels, restaurants, transportation, handicrafts, and so on that can create jobs and develop the economic sector. Indonesia has 231 million people with the Islamic religion, this is very influential on the tourism industry. The Mastercard Crescentrating Global Travel Market Index (GMTI) in its 2019 report stated that in 2026 it is predicted that there will be 230 million Muslim tourists globally who will travel, so every region or country must be prepared for this. This research is a quantitative study using primary data through the distribution of questionnaires with the aim of setting the intention of traveling the Muslim community from Batam City to Bali Island. The data that was successfully collected was 400 data and tested using the SPSS application. The test results found that the variables religiosity, attitude towards non-Muslim cities, halal have a risk of influencing the intention of traveling Muslim communities from Batam City to Bali Island.